Pengaruh Halal Awareness Dan Social Media Marketing Terhadap Minat Beli Pada Mixue - Nadya Rahma Agustiani; Viola De Yusa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of Halal Awareness and Social Media Marketing on the intention to buy MIXUE. This type of research is quantitative causality using multiple regression analysis. The population of this study was the people of Bandar Lampung with a sample of 120 respondents who were taken using a purposive sampling technique. The results in this study indicate that the Halal Awareness variable has no effect on the intention to buy MIXUE. Social Media marketing variables affect the intention to buy MIXUE.